Analysis of Temporal Changes of Air Pollutants Concentrations in Kocaeli, Turkey - Özer Akyürek (Doğal Afetler ve Çevre Dergisi, 2025)
Air is an essential requirement for living things to survive. Air pollution is defined as the foreign substances in the air reaching a quantity and density above normal. Regular monitoring and analysis of air pollution is an indispensable step for the measures and policies to be taken. In recent years, the use of open-source software in the evaluation and analysis of air quality data has increased. The R software-based Openair Package developed by the Environmental Research Group at King's College London. This package is used to analyze air quality data, identify potential pollutant sources, and identify correlations and statistical relationships between parameters. In this study, the hourly pollutant parameter (PM, SO2, and NOx) measured from two air quality stations between 2018 and 2022 in Kocaeli, were analyzed temporally and statistically with the Openair Package. The study found that the primary sources of pollutants are anthropogenic activities such as vehicle traffic, fossil fuels used for heating, and natural resources. As a result of the analysis, a decrease in PM concentrations and an increase in SO2 concentrations were observed during the study period. In addition, it was determined that traffic density has a linear relationship with the NOx parameter.